(untitled) (Global Journal of Medical Research, 2018)
The size of teeth, when smaller than normal is termed as microdontia. Microdontia involving a single tooth is frequently seen. It commonly affects the maxillary lateral incisor and the third molars. A common form of microdontia which affects the maxillary lateral incisor is known as "peg lateral." But localized involvement of mandibular lateral incisor is very rare entity in itself. Hence, this article describes a rare finding of microdont mandibular lateral incisor in a 9-year-old Indian female.